A prospective cohort study on symptoms of common mental disorders among current and retired professional ice hockey players - Gouttebarge, V.; Kerkhoffs, G. M. M. J. (The Physician and Sportsmedicine, 2017)
Objectives: Scientific knowledge about symptoms of common mental disorders in professional ice hockey is lacking. Consequently, the primary aims of the study were to (i) determine the prevalence, comorbidity and 6-month incidence of symptoms of common mental disorders (distress, anxiety/depression, sleep disturbance, adverse alcohol use, eating disorders) among current and retired professional ice hockey players and (ii) evaluate their potential relation with potential stressors (severe musculoskeletal injuries, surgeries, recent life events, career dissatisfaction).